Green technology implementation: The impact of communication networks and technology characteristics - Abidin, Rahimi; Jusoh, Muhammad Shahar; Amlus, Mohamad Harith; Ismail, M.S. (AENSI Publisher, 2014)
Malaysia was, in fact, among the first Southeast Asian nations to slot in environmental concerning actors and factors in its long-range economic plans and strategies.To develop green technology the government takes some effective initiatives like the establishment of a great amount of fund to provide soft loan to companies that supply and utilized green technology.However, adopting of environment friendly technology can be slow if the new technological innovations are not impressive in terms of the firms" inducements, or if the firms do not have adequate data and information to evaluate whether or not switching to a green technology is in their private interests, to analyze their cost and benefits regarding new measures.Adoption of green technologies might encompass a high degree of uncertainty and, warrants considerable attention within a manufacturing company at the strategic level. Hence, the process to attain required way to achieve achievement with this technology is an issue that demands to be investigated.With the aim of providing information on the subject matter, this paper put it full phase efforts and concentrations on the influence of the two factors on green technology adoption. These factors are technology characteristics and communication networks.Based on the data analysis from a survey conducted on a sample of 76 companies, it was found that there are significant relationships between the two factors and green technology implementation.